Deterministic Mechanisms, the Revelation Principle, and Ex-Post Constraints - Felix Jarman; Vincent Meisner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
This note establishes a revelation principle in terms of payoff for deterministic mechanisms under ex-post constraints: the maximal payoff implementable by a feasible deterministic mechanism can also be implemented by a feasible deterministic direct mechanism.
Keywords: D82; 330; mechanism design; revelation principle; ex-post constraints